2010
DOI: 10.1016/j.jcrs.2010.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Phacoemulsification with intraocular lens implantation in patients with uveitis

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 25 publications
2
38
1
1
Order By: Relevance
“…However, modern surgical techniques allows for IOL placement in well selected cases. A retrospective series of 108 eyes with various causes of uveitis demonstrated a 21% incidence of clinical PCME, with 74% achieving final visual acuity of 20/40 or better [16]. In a prospective cohort of 41 eyes with uveitis and 52 without uveitis, Belair et al [4] demonstrated that the incidence of PCME on OCT at 3 months postoperatively was 8 and 0%, respectively (P ¼ 0.08).…”
Section: Risk Factorsmentioning
confidence: 98%
“…However, modern surgical techniques allows for IOL placement in well selected cases. A retrospective series of 108 eyes with various causes of uveitis demonstrated a 21% incidence of clinical PCME, with 74% achieving final visual acuity of 20/40 or better [16]. In a prospective cohort of 41 eyes with uveitis and 52 without uveitis, Belair et al [4] demonstrated that the incidence of PCME on OCT at 3 months postoperatively was 8 and 0%, respectively (P ¼ 0.08).…”
Section: Risk Factorsmentioning
confidence: 98%
“…Ram et al, 2010, report an incidence of macular edema of 21.3 % and Estafanous et al, 2001, reported one of 33 % following phacoemulsification. Bhargava et al, 2013, report an incidence of 14.8 % following manual SICS in patients with uveitis.…”
Section: Complicationsmentioning
confidence: 99%
“…Pro-inflammatory molecules such as plasma phospholipids, interleukins, phospholipases, and cytokines can cause an increase in the lens epithelial permeability and development of cataract [3]. Among patients with uveitic cataract, performing cataract surgery is a challenge due to related complications like recurrent uveitis, raised intraocular pressure or hypotony, small pupil, and posterior synechiae, among others [4,5]. Cataract surgery in patients with uveitis may lead to postoperative flare up of inflammation and macular edema leading to a suboptimal visual outcome.…”
Section: Editorialmentioning
confidence: 99%